2016
DOI: 10.1161/strokeaha.116.014330
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease Burden Is Increased in Systemic Lupus Erythematosus

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 42 publications
4
48
0
1
Order By: Relevance
“…The approach was first introduced by Staals et al . to prove the association between cSVD and lacunar stroke subtype in ischaemic stroke patients and then was widely used in studies focusing on the relationship between cSVD and systemic lupus erythematosus, aortic atheroma and mild parkinsonian signs . As far as is known, the findings here are the first not only to describe the total burden of cSVD in primary ICH but also to assess the impact of overall cSVD damage on R‐DWILs.…”
Section: Discussionmentioning
confidence: 93%
“…The approach was first introduced by Staals et al . to prove the association between cSVD and lacunar stroke subtype in ischaemic stroke patients and then was widely used in studies focusing on the relationship between cSVD and systemic lupus erythematosus, aortic atheroma and mild parkinsonian signs . As far as is known, the findings here are the first not only to describe the total burden of cSVD in primary ICH but also to assess the impact of overall cSVD damage on R‐DWILs.…”
Section: Discussionmentioning
confidence: 93%
“…It remains unclear whether the Ab in accumulated plaque in the cortical blood vessels is derived from the circulation, the blood vessel wall itself, or from the central nervous system 30 A disadvantage associated with using EC-APP770 + mice is the increased expression of Aiolos due to insertion of the floxed APP transgene within the intron of the gene encoding for Aiolos, Ikzf3. Aiolos overexpression has been reported in B cells from patients with systemic lupus erythematosus (SLE) 36 , while it was recently shown that the cerebral small blood vessel disease burden is increased in SLE 37 . By crossing with AD model mice, both EC-APP770 + and EC-APP770mice exhibited amyloid plaques in the cerebral small blood vessels, an effect that is likely related to the SLE-like features.…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI acquisition parameters were broadly the same across all participant groups and have been described in detail previously. 11,14,16,17 The brain health index…”
Section: Brain Mri Acquisitionmentioning
confidence: 99%